The Hsp90 inhibitor 17-DMAG decreases infection of porcine circovirus type 2 in mice. (August 2017) - Liu, Jie; You, Jinwei; Zhang, Xuliang; Ma, Chang; Dong, Min; Chen, Li; Jiang, Ping; Yun, Shifeng
Abstract: Although several factors affecting porcine circovirus type 2 (PCV2) infection have been reported, their precise roles are far from clear. The aim of this study was to determine whether 17-dimethylaminoethylamino-17-demethoxygeldanamycin (17-DMAG), an inhibitor of Hsp90, could significantly affect PCV2 infection and immune responses in BALB/c mice. Intraperitoneal injection of 17-DMAG significantly reduced viral loads in the blood and tissues of mice infected with PCV2, compared with control groups. The 17-DMAG treatment decreased serum interleukin (IL)-10 and tumor necrosis factor(TNF)-α levels, but it did not have a significant effect on the IL-1β level. These data demonstrate that 17-DMAG is highly effective in suppressing PCV2 replication in BALB/c mice, indicating that it has potential value as an antiviral drug against PCV2 infection. Highlights: Hsp90 inhibitor (17-DMAG) could reduce the PCV2 content in blood. 17-DMAG treatment weakened PCV2 infection in different tissues. 17-DMAG could regulate immune responses that are normally stimulated by PCV2 replication.